Love, madness, and scandal : - Luthman, Johanna (oxford university press, 2017)
The high society of Stuart England found Frances Coke Villiers, Viscountess Purbeck (1602-1645) an exasperating woman. She lived at a time when women were expected to obedient, silent, and chaste, but Frances displayed none of these qualities. Her determination to ignore convention contributed in no small measure to a live of high drama, one which encompassed kidnappings, secret rendezvous, an illegitimate child, accusations of black magic, imprisonments, disappearances, and exile, not to mention court appearances, high-speed chases, a jail-break, deadly disease, royal fury, and-- by turns-- religious condemnation and conversion. On one level a thrilling tale of love and sex, kidnapping and elopement, the life of Frances Coke Villiers is also the story of an exceptional woman, whose personal experiences intertwined with the court politics and religious disputes of a tumultuous and crucially formative period in English history.